The Impact of Foreign Direct Investment on the Economic Growth of Egypt (1980-2018) - Alaa, Safwat; Ashraf, Salah; Marwa, Elsherif (International Journal of Economics and Financial Issues, 2021)
Many developments had occurred in the global economy. Among these developments is the increase of capital flows across countries. Foreign direct investment (FDI) is considered to be one of the cross border capital flows that countries use in order to enhance their economic growth. This study focuses on how FDI impacts the economic growth of Egypt for a period from 1980 to 2018. The study applies Johansen co-integration, Vector Error Correction Model (VECM) and Ganger causality in the methodology. Johansen co-integration results show that a long run relationship exists among the variables. In addition, VECM shows that FDI exerts a positive significant impact on the economic growth of Egypt. Finally, a bidirectional causality between FDI and the economic growth of Egypt is shown by Granger causality. Keywords: Foreign Direct Investment, Economic Growth, Johansen Co-integration, Vector Error Correction Model, Granger Causality Test JEL Classifications: C32, F6, F21, O11, O16 DOI: https://doi.org/10.32479/ijefi.11762